CircRNA_1809 promotes the osteogenic differentiation of bone marrow mesenchymal stem cells through miR-370-3p - Lei Zhang; Yidan Xu; Ningning Liu; Mengjie Xu; Refeina Tuerxun; Mireyeti Shahatibieke; Yuan Yao (Scientific Reports)
Abstract Circular RNA (circRNA) is a unique closed ring structure of noncoding RNA. Although many human diseases have been confirmed to be inextricably linked with circRNAs, whether circRNAs have a potential regulatory function in the osteogenic differentiation of bone marrow mesenchymal stem cells (BMMSCs) remains to be further elucidated. In a previous study by our team, all the differentially expressed circRNAs and messenger RNAs (mRNAs) involved in the osteogenic differentiation of BMMSCs were identified via high-throughput sequencing, and a competing endogenous RNA (ceRNA) regulatory network was constructed via bioinformatics analysis. The circRNA_1809/miR-370-3p/Kitlg axis may be involved in regulating the osteogenic differentiation of BMMSCs. In this study, gene knockdown/overexpression, small interfering RNA (siRNA) transfection and mimic/inhibitor treatment were used to evaluate the regulatory effects of circRNA_1809 on the miR-370-3p/Kitlg pathway and the osteogenic differentiation of rat bone marrow mesenchymal stem cells (rBMMSCs) in vitro. The results revealed that circRNA_1809 was upregulated and that miR-370-3p was downregulated during the osteogenic differentiation of rBMMSCs. The low expression of circRNA_1809 significantly downregulated the expression of Kitlg and decreased the protein expression of ALP and RUNX2. The expression of miR-370-3p was negatively correlated with the expression of Kitlg in rBMMSCs and the ability to undergo osteogenic differentiation. In addition, a dual-luciferase assay confirmed the binding of miR-370-3p and circRNA_1809, and si-circRNA_1809 + miR-370-3p inhibitor cotransfection reversed some of the downregulation of Kitlg induced by si-circRNA_1809, whereas si-circRNA_1809 + miR-370-3p mimic increased the downregulation of Kitlg. Therefore, circRNA_1809 may promote the expression of Kitlg by regulating miR-370-3p and subsequently promote the osteogenic differentiation of rBMMSCs.